Death and institutions : processes, places and the past - Woodthorpe, Kate; Frisby, Helen; Michael-Fox, Bethan (Bristol University Press, 2025)
Institutions play a crucial role in shaping experiences of end-of-life care, dying, death, body disposal and bereavement. However, there has been little holistic or multidisciplinary research in this area, with studies typically focusing on individual settings such as hospitals and cemeteries, or being confined to specific disciplines. This interdisciplinary collection combines chapters on process, place and the past to examine the relationships both within and between institutions, institutionalization and death in international contexts. Of broad appeal to students and academics in areas including social policy, health sciences, sociology, psychology, anthropology, cultural studies, history and the wider humanities, this collection spans multiple disciplines to offer crucial insights into the end of life, body disposal, bereavement and mourning.
Keywords: Death.; Bereavement.; Bereavement -- Psychological aspects.; Death (Biology); Death -- History.; Ethnology -- Death.; Deuil.; Deuil -- Aspect psychologique.; Mort (Biologie); mourning.; SOCIAL SCIENCE / Death & Dying.